Nitrogen-Doped Biomass-Derived Carbon Formed by Mechanochemical Synthesis for Lithium–Sulfur Batteries - Schneidermann, Christina; Kensy, Christian; Otto, Pascal; Oswald, Steffen; Giebeler, Lars; Leistenschneider, Desiree; Graetz, Sven; Doerfler, Susanne; Kaskel, Stefan; Borchardt, Lars (Chemsuschem, 2019)
Nitrogen-doped carbons were synthesized by a solvent-free mechanochemically induced one-pot synthesis by using renewable biomass waste. Three solid materials are used: sawdust as a carbon source, urea and/or melamine as a nitrogen source, and potassium carbonate as an activation agent. The resulting nitrogen-doped porous carbons offer a very high specific surface area of up to 3000 m 2 g −1 and a large pore volume up to 2 cm 3 g −1 . Also, a high nitrogen content of 4 wt % (urea only) up to 12 wt % (melamine only) is generated, depending on the nitrogen and carbon sources. The mechanochemical reaction and the impact of different wood components on the porosity and surface functionalities are investigated by nitrogen physisorption and high-resolution X-ray photoelectron spectroscopy (XPS). These N-doped carbons are highly suitable as cathode materials for Li–S batteries, showing high initial discharge capacities of up to 1300 mAh g sulfur −1 (95 % coulombic efficiency) and >75 % capacity retention within the first 50 cycles at low electrolyte volume.
CRIS-Team Scopus Importer:2022-04-14
Keywords: batteries; biomass; energy storage; lithium; mechanochemistry